Traveling heavy : a memoir in between journeys - Behar, Ruth, 1956- (Duke University Press, 2013)
In Ruth Behar's intimate, unconventional memoir, poignant memories of growing up as an immigrant child come together with reflections on being a traveling anthropologist who cherishes the kindness of strangers.